A Curriculum Alignment Analysis: A Sample of Life Sciences Course Curriculum (2018) for 3rd-Grade Students - Ferat YILMAZ; Meral ÖNER SUNKUR (Anı Publishing, 2021)
In this study, the analytical research design is used to conduct a curriculum alignment analysis on the Life Sciences Course Curriculum (LSCC) for 3rd-grade according to Revised Bloom's Taxonomy (RBT). Objective elements were sampled from LSCC. Class instructional activities and assessment questions were taken from the Life Sciences course book for 3rd-grade students, published by Evren Publishing and approved by the Board of Education and Discipline. In this research, 29 cognitive objectives were studied in addition to 134 instructional activities and 90 assessment questions relating to those cognitive objectives. These elements were analyzed by two researchers and using RBT matrix. The findings showed that among the objectives, instructional activities and assessment questions in LSCC, there were nine objectives with complete alignment, 17 objectives in partial alignment and three objectives with misalignment.